Repetition and Emotive Communication in Music Versus Speech - Margulis, Elizabeth Hellmuth (Frontiers in Psychology, 2013)
Music and speech are often placed alongside one another as comparative cases. Their relative overlaps and disassociations have been well explored (e.g. Patel, 2010). But one key attribute distinguishing these two domains has often been overlooked: the greater preponderance of repetition in music in comparison to speech. Recent fMRI studies have shown that familiarity – achieved through repetition – is a critical component of emotional engagement with music (Pereira et al., 2011). If repetition is fundamental to emotional responses to music, and repetition is a key distinguisher between the domains of music and speech, then close examination of the phenomenon of repetition might help clarify the ways that music elicits emotion differently than speech.